Nivel de conocimientos y práctica de autocuidado en pacientes hemodializados del Hospital General Isidro Ayora de Loja - Macas Quituizaca, Cristhian Darwin (2020)
Kidney failure is the loss of kidney function, causing the incorrect excretion of residual metabolic products and fluids from the body, resulting in alterations in the functions of the body´s organs. Hemodialysis is a replacement treatment of the kidney function that involves filtering the blood periodically. While it lasts, the blood is extracting from the body and circulated through the dialyzer, or filter, where accumulated toxins and excess fluids are removed. The general objective of the present study was to determine the knowledge and practices of self-care in hemodialysis patients of the General Hospital Isidro Ayora of Loja for the period November 2019- April 2020. It was a descriptive- transversal study, where the sample was 66 people, to whom it was applied a survey. The results determined that 68.2% come from urban areas, in relation to marital status the 57.5% are married, 66.7% are male, 48.5% have primary education and 65% are aged between 51 to 70 years. As to knowledge level about self-care 71.20% have a high knowledge, in relation to kidney disease, hemodialysis, vascular access, diet, exercise and reaction to medical treatment. Concerning to self- care practices 74.20% have adequate hygiene, care of the fistula, adequate diet, exercise and medical treatment. Key words: Users, kidney failure, attitudes, renal replacement therapy.